The Effect of Utilization of Social Media Instagram @Nanarfshop on Buying Interest of Fisipol Students University Ekasakti Padang - Rahmayani, Okta; Syaiful Ardi; Reski Nofrialdi (Dinasti Research, 2022)
Social networking sites are one type of virtual communication that helps individuals connect with others. One of the most popular social networking sites and has the most users worldwide is Instagram. Instagram, which was previously only used by users to share personal photos, has now turned into a means of selling online. In addition to communicating with the closest people, Instagram is also an option for selling stalls. Along with the increase in Instagram users in recent years, many Instagram users use it for online shopping. Students as Instagram users shop a lot online such as clothes, pants, shoes and other items. This study was conducted to find out how much influence Instagram @nanarfshop has on the buying interest of Fisipol students, Ekasakti University, Padang. This type of research is descriptive research with a quantitative approach. The sampling technique used is proportional random sampling, namely sampling from all members of the population is carried out randomly without regard to the strata in the population. The sample in this study was 71 people by distributing questionnaires or questionnaires to Fisipol students, Ekasakti University, Padang. The data were analyzed using statistical methods with the help of SPSS (Statistics Product And Service Solutions) Version 22.0 software. This study shows the hypothesis that there is an influence between the Instagram @nanarfshoop social media variable on the buying interest of Fisipol Students, Ekasakti University Padang by 97% and the rest is influenced by other variables by 3% not in this study.